Uganda Economic Update, April 2016 : Unleashing the Power of Public Investment Management - World Bank (World Bank, Washington, DC, 2016)
This Seventh Edition of the Uganda Economic Update discusses the importance of accompanying fiscal strategy with sound public investment management systems. Indeed, a key risk to Uganda's fiscal strategy relates to the potential for public investments to fail to yield the expected growth and welfare dividend. Over the past decade, for every dollar invested in Uganda’s capital infrastructure, only seven-tenth of a dollar has been generated. This is far below countries that have successfully undergone structural transformation. As an example, every dollar invested in the development of the interstate highway network in the United States of America between 1954 and 2001, generated six dollars’ worth of economic activity. In other words, Uganda's public investments are falling short of generating the desired economic return. The good news is that by improving public investment management, Uganda can greatly increase her economic growth rate and social impact of her investment strategy.